Recent Patents on Immobilized Microorganism Technology and Its Engineering Application in Wastewater Treatment - An, Taicheng; Zhou, Lincheng; Li, Guiying; Fu, Jiamo; Sheng, Guoying (Recent Patents on Engineering, 2008)
Compared with suspended microorganism technology, immobilized microorganism technology possesses many advantages, such as high biomass, high metabolic activity, and strong resistance to toxic chemicals, and so on. This review presents the state of the art of various immobilized microorganism methods as well as immobilization microorganism carriers whose engineering applications are mainly focused on bioreactors including fluidized bed reactor (FBR) and packed bed reactor (PBR). This review covers the patents which emphasize the characteristic of the immobilization carriers as well as bioreactors from the year of 2000 up to date. In the last part of the review, the future developing trend in immobilization microorganism technology and the potential engineering applications in wastewater treatment were also proposed tentatively.
Keywords: Immsobilization microorganism